Tuning the photomechanical behavior and excellent elasticity of azobenzene via cocrystal engineering. Issue 46 (16th November 2020) - Ye, Yang; Gao, Lei; Hao, Hongxun; Yin, Qiuxiang; Xie, Chuang
Abstract : Obtaining crystals with different photomechanical responses and excellent mechanical properties simultaneously through cocrystal engineering based on the same photoactive molecule. Abstract : Adjusting the photomechanical behavior and mechanical properties of photoactive crystals is a challenging goal, especially for the same photoactive molecule. In this study, cocrystals of 4-aminoazobenzene (AAB) with a series of coformers containing pyridyl groups were designed to tune its photobending behavior and elasticity. 5 AAB-based cocrystals exhibiting different photomechanical behaviors and elasticity were obtained. The structure-related bending behaviors of these cocrystals were correlated to the dihedral angles between AAB molecules and the bending faces. A rarely observed photoinduced curling was discovered on the AAB–4, 4′-bipyridine (BIP) cocrystal according to this structure–property correlation. Excellent elasticity was achieved on the AAB–4-(1-naphthylvinyl)pyridine (NPE) cocrystal. The molecular mechanism analysis revealed that the formation of large dispersive weak interactions and molecular interlocking are essential to improving the elasticity. Typical irreversible plastic deformation was found on the AAB–BIP cocrystal which was attributed to the appearance of slip planes connected via weak interactions. This demonstrated that the photomechanical properties and elasticity are closely related to the supramolecular packing and can be tuned via cocrystallization. Cocrystallization and the results of this work could be useful to expand the variety of photomechanical molecular crystals, and tune the photobending behavior and improve the elasticity of molecular crystals.